Hereditary Pigmentary Degeneration (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The review article examines the genetic aspects of the development of retinitis pigmentosa, a hereditary retinal pathology that can have different types of inheritance and can cause disability and reduce the quality of life of patients. The genetic basis for the development of this group of degenerative conditions can be a number of mutations. The pathogenesis of retinitis pigmentosa is quite complex and requires detailed study, taking into account the morphology and functioning of photoreceptor cells - rods.